Ultrawide color gamut LCD display with CdSe/CdS nanoplatelets. Issue 10 (2nd April 2019) - Wen, Zuoliang; Fang, Fan; Zhang, Chaojian; Ding, Shihao; Sun, Jiayun; Tang, Haodong; Xu, Bing; Wang, Kai; Teo, Kie Leong; Sun, Xiao Wei
Abstract: We present a liquid‐crystal display (LCD) backlight made of nanoplatelets (NPLs) for the first time. Owing to the narrow emission linewidth of NPLs (8‐12 nm) and quantum dots (QDs), the spectrum exhibits a wide color gamut display with a 139.9% color gamut of National Television System Committee (NTSC) 1953 standard and 104.5% Rec.2020 (ITU‐R Recommendation BT.2020), realizing a truly ultrawide color gamut LCD display. Abstract : We present a liquid‐crystal display (LCD) backlight made of nanoplatelets (NPLs) for the first time. Owing to the narrow emission linewidth of NPLs (8‐12 nm) for green and quantum dots (QDs) for red, the display exhibits a wide color gamut area of 139.9% of National Television System Committee (NTSC) and 104.5% of Rec.2020, realizing a truly ultrawide color gamut LCD display.